2019
DOI: 10.1159/000496438
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of TGF-β-Activated Kinase 1 and MAP3K7 Binding Protein 3 in Peanut-Specific T-Cell Responses

Abstract: Peanut allergy is considered to be the most common cause for food-induced anaphylaxis. Currently, no approved treatment is available. Avoidance is the only measure to prevent anaphylactic reactions to peanuts. T-helper cells are of special importance for the sensitization process and the maintenance of allergic inflammation. Identifying markers of allergen-specific T-cell responses may help to develop novel treatment approaches. Therefore, we aimed to define new T-cell target genes in Ara h 2-specific T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As CD24 + CD38 hi B cells increased dramatically during Peg-IFNα-2b therapy, we further investigated whether these CD24 + CD38 hi B cells are relevant for clinical outcomes. CD24 + CD38 hi B cells are found at low frequencies (<5% of B cells) in normal healthy human controls ( 34 ). Depending on whether the percentage of CD24 + CD38 hi B cells in HBV patients at 72 weeks after the start of PEG-IFNα-2b therapy are higher than that in the normal healthy controls or not, patients were classified into the more CD24 + CD38 hi B cell group (CD24 + CD38 hi B cells ≥ 5% of B cells) or the fewer CD24 + CD38 hi B cell group (CD24 + CD38 hi B cell <5% of B cells).…”
Section: Resultsmentioning
confidence: 99%
“…As CD24 + CD38 hi B cells increased dramatically during Peg-IFNα-2b therapy, we further investigated whether these CD24 + CD38 hi B cells are relevant for clinical outcomes. CD24 + CD38 hi B cells are found at low frequencies (<5% of B cells) in normal healthy human controls ( 34 ). Depending on whether the percentage of CD24 + CD38 hi B cells in HBV patients at 72 weeks after the start of PEG-IFNα-2b therapy are higher than that in the normal healthy controls or not, patients were classified into the more CD24 + CD38 hi B cell group (CD24 + CD38 hi B cells ≥ 5% of B cells) or the fewer CD24 + CD38 hi B cell group (CD24 + CD38 hi B cell <5% of B cells).…”
Section: Resultsmentioning
confidence: 99%
“…54 Another study reported that TGFbeta-activated kinase 1 and MAP3K7 binding protein 3 (TAB3) has been linked to T cells in peanut allergy. 55 Moreover, the Barwon Infant Study (BIS) showed that the proportion of naïve regulatory T cells at birth could be used as a marker of food allergy development in infancy. 56 This adds to the established role of regulatory cell subsets early in life.…”
Section: T-cell Epitopes and Subsets Can Distinguish Between Allergicmentioning
confidence: 99%
“…In a different approach, the inhibitory transmembrane protein, which is part of the immunoglobulin superfamily CD200R, has been identified as a highly upregulated marker on peanut‐specific T cells, Th2, Tc2, ILC2, and basophils . Another study reported that TGF‐beta–activated kinase 1 and MAP3K7 binding protein 3 (TAB3) has been linked to T cells in peanut allergy . Moreover, the Barwon Infant Study (BIS) showed that the proportion of naïve regulatory T cells at birth could be used as a marker of food allergy development in infancy .…”
Section: Introductionmentioning
confidence: 99%